(untitled) - Meislich, Herbert (New York, 1993)
The book provides strategies for solving tough problems in oraganic chemistry in step-by-step detail
Keywords: Chemistry,Chemistry Organic; Outlines, syllabi, etc,Problems, exercises, etc